Pengaruh Keputusan Investasi, Pendanaan dan Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Pada Perusahaan Sektor Consumer Goods dan Basic Industry and Chemicals yang Tercatat Aktif Di Bursa Efek Indonesia Tahun 2012-2014) - Tridewi, Afifa Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The main of this research is to know how the impact of financial management to value of firm. Based on Moeljadi (2006) there are some aspects in financial management they are : investment decision, financial decision and dividend policy. Based on previews study there some different result that financial management doesn’t have impact to financial management, so in this research to get result about the impact of financial management to value of firm. The method used in this research is path analysis to determine the direct and indirect effect between dependent and independent variables. Investment decisions are calculated through the PER (Price Earning Ratio), the funding decision is confirmed by DER (Debt To Equity Ratio), the dividend policy is confirmed through the Dividend Payout Ratio while Dependent Variables are confirmed through the Corporate Value Price Book Value. From this study showed that the investment and financing decisions affect the value of the dividend policy of the company but does not affect the value of the company. Investment decisions take effect for the investment decision will happen investments that will increase the company's profits, and funding decisions impact on the source of funds used while the dividend policy does not affect the niali company in accordance with the theory of dividends is not relevant where the dividend policy is only the ratio of the details of the payment of dividends and does not affect shareholder wealth. Keywords : investment decision, financial decision, dividend policy, value of firm.